ANALISIS AKTIVITAS GURU PADA PEMBELAJARAN BIOLOGI SMA NEGERI 1 BENAI MATERI STRUKTUR DAN FUNGSI JARINGAN TUMBUHAN PASCA PEMBELAJARAN TATAP MUKA TERBATAS (PTMT) PANDEMI COVID-19 - Hestiyani Hestiyani; Wan Syafi’i; Riki Apriyandi Putra (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: The low learning activity of students in learning material structure and function of plant tissue is caused by two factors. First, the role of the teacher is too dominating. During learning activities on the structure and function of plant tissue, the teacher uses a direct learning model that is teacher-centered and involves a lot of one-way communication. Second, there is a lack of teacher variation in using the media in carrying out learning activities. This study aims to determine the biology learning of SMA Negeri 1 Benai students on the structure and function of plant tissue after limited face-to-face learning (PTMT) of the Covid-19 pandemic. The research was conducted in class X MIPA 3 and XI MPA 4 SMA Negeri 1 Benai in August-September 2022. Data collection instrument was collected by observing, interviewing and documenting. The results of the study were used to determine teacher activity in biology learning at SMA Negeri 1 Benai on the structure and function of plant tissue after limited face-to-face learning (PTMT) of the Covid-19 pandemic. This study used a test of the credibility of reference materials, member check credibility and descriptive analysis. The conclusion obtained from the activities of teachers in the field of study when studying the structure and function of plant tissue is good with an average of 76.01%.Key Word: Analysis, Biology Learning, Teacher Activities